Analisis Pengembangan dan Penataan Pasar Tradisional (Studi Kasus Pasar Terminal Induk Handil Bakti Kabupaten Barito Kuala) - Melinda, Nurhinsa; Yunani, Ahmad (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The Main Terminal Market is a central market that sells various kinds of goods. Raw goods, semi-finished goods or finished goods can be found in this market. The Main Terminal Market is located in Alalak District, Barito Kuala Regency, South Kalimantan. The Main Terminal Market operates every Sunday. Development and structuring is ongoing for this market. Descriptive quantitative method was conducted to determine the impact of development and arrangement on this market, seen from the perception of market visitors, traders' income, and the efforts made by the government for the market. The Main Terminal Market is still in need of development and arrangement until now.